Which "industrial policies" are meaningful for Latin America? - Marcelo de Paiva Abreu (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2005)
This paper's main concern is to assess which "industrial policies" would be meaningful for Latin America nowadays. The first section considers definitions of "industrial policies" and their nature in the past. The second section centers on national growth experiences that may serve as paradigms for LAC economies. Section 3 is on economies which are growth paradigms and on their relevant policies. Section 4 is on present multilateral constraints on "industrial policies", especially in the case of subsidies and trade-related investment measures, as these have been considerably tightened as a result of the Uruguay Round of multilateral trade negotiations. The following section analyses the link between macroeconomics and "industrial policies" both in relation to limitations imposed by macroeconomic instability on industrial policy and to how growth depends on the cost of investment on both micro and macroeconomic factors. Section 6 analyses industrial policy alternatives. The paper concludes with section 7 which is on policy recommendations seeking to improve criteria to pick winners where market failures are especially costly.
Keywords: 330; Industriepolitik; Lateinamerika